2020
DOI: 10.1080/08995605.2020.1724753
|View full text |Cite
|
Sign up to set email alerts
|

A quasi-experimental study to explore the impact of PAR on becoming an Agile Warrior

Abstract: application of constructivist approaches to training within the Armed Forces, paying particular attention to the motivational climate of the learning environment and the learning factors and predispositions of the learners. Further studies are needed to examine the impact of constructivist approaches to training within that context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…The RTQ is a reliable, valid instrument for assessing the impact of an instructional design approach “Present, Apply, Review” on becoming agile warriors (The Agile Warrior is a soldier who can make decisions for themselves, as opposed to waiting for orders from senior officers). This questionnaire has even been validated in nursing school settings (Berry et al, 2020; Lethbridge et al, 2013), and the Persian version was confirmed by Ghanizadeh and Jahedizadeh (2017) while the RTQ was conducted in similar settings by Buzdar and Ali (2013), where it was also confirmed for validity and reliability. Meanwhile, in the present study, the Cronbach’s alphas indicated reasonable reliability for the RTQ, and only one factor, HA, showed a lower reliability than other factors (0.69).…”
Section: Discussionmentioning
confidence: 87%
“…The RTQ is a reliable, valid instrument for assessing the impact of an instructional design approach “Present, Apply, Review” on becoming agile warriors (The Agile Warrior is a soldier who can make decisions for themselves, as opposed to waiting for orders from senior officers). This questionnaire has even been validated in nursing school settings (Berry et al, 2020; Lethbridge et al, 2013), and the Persian version was confirmed by Ghanizadeh and Jahedizadeh (2017) while the RTQ was conducted in similar settings by Buzdar and Ali (2013), where it was also confirmed for validity and reliability. Meanwhile, in the present study, the Cronbach’s alphas indicated reasonable reliability for the RTQ, and only one factor, HA, showed a lower reliability than other factors (0.69).…”
Section: Discussionmentioning
confidence: 87%
“…While learning design is definitely important, how teachers implement such learning designs may substantially impact the eventual learning outcomes. For example, in a large quasi-experimental design exploring a new teaching innovation in the British Army, Berry et al (2020) explored whether a present-act-reflect (PAR) approach could encourage more self-reflection and critical thinking among 134 recruits relative to 177 recruits who were trained in the traditional model. In contrast to expectations, recruits in the experimental condition did not significantly increase their self-reflection and critical thinking skills in a pre/post test design.…”
Section: Designing Police Effective Learning Programmes Based On the Preferences Of Professional Learnersmentioning
confidence: 99%
“…In contrast to expectations, recruits in the experimental condition did not significantly increase their self-reflection and critical thinking skills in a pre/post test design. Qualitative follow-up interviews indicated that many PAR trained instructors mostly referred back to their traditional teaching style (Berry et al, 2020).…”
Section: Designing Police Effective Learning Programmes Based On the Preferences Of Professional Learnersmentioning
confidence: 99%